Oocyte ERM and EWI Proteins Are Involved in Mouse Fertilization - Cohen, J; Wang, L; Marques, S; Ialy-Radio, C; Barbaux, S; Lefèvre, B; Gourier, C; Ziyyat, A (Frontiers in Cell and Developmental Biology, 2022)
In mammalian fertilization, the link between the oocyte plasma membrane and underneath cytoskeleton has often been associated to key elements of successful gamete fusion, like microvilli shaping or CD9 function, but its effective role has poorly been studied. EWI-2 and EWI-F as cis partners of CD9, and ERM proteins (Ezrin, Radixin and Moesin) that both attach to the actin cytoskeleton and to the EWI are part of the molecules that make the link between the oocyte membrane and its cytoskeleton. This study aims to assay through siRNA inhibition, the involvement of these ERM and EWI molecules in mouse fertilization, their role in the microvilli morphology of the egg but also their possible contribution to the cortical tension, a parameter that reflects the mechanical behavior of the oocyte cortex. Whereas inhibiting separately the expression of each protein had no effect on fertilization, the combined inhibition of either EWI-2/ EWI-F or the three ERM triggered a significant decrease of the fertilization index. This inhibition seems to correlate with an increase in the radius of curvature of the oocyte microvilli. It also causes a decrease of the oocyte cortical tension. These results show the importance of EWI-2 and EWI–F and ERM proteins in the smooth running of a fertilization event and support their involvement in the microvilli architecture of the oocyte and in its mechanical properties of the oocyte.